Enhancing umrah pilgrim satisfaction through effective logistic services and inventory management - Saputri, Riska; Febrian, Andis (Journal of Islamic Economics Management and Business (JIEMB), 2023)
This study explores the impact of logistic services and inventory management on the satisfaction of umrah pilgrims at PT. Asyesa Hasanah Tour & Travel Sumatera Barat. The research addresses the need for effective logistics management in the umrah travel industry, highlighting its importance in providing timely and quality services to pilgrims. Utilizing a quantitative approach, data were collected from 85 respondents among a population of 536 umrah pilgrims. The study found that logistic services, characterized by reliability, timeliness, and resource availability, significantly enhance pilgrim satisfaction. Similarly, efficient inventory management, involving precise planning, control, and distribution of goods, also positively impacts satisfaction levels. The findings suggest that both logistic services and inventory management are critical in ensuring high levels of customer satisfaction. The study concludes that umrah travel companies should continuously improve their logistic and inventory management strategies to maintain competitive advantage and meet the evolving needs of their customers. This research contributes to the literature by providing detailed insights into the operational components of logistics and inventory management within the context of umrah travel, emphasizing the role of technology and employee satisfaction in enhancing service delivery.